Perlindungan Hukum bagi Konsumen atas Pemalsuan Registrasi BPOM Pangan Olahan: Perbandingan Regulasi Indonesia dan Malaysia - Revinka Simatupang; Winda Fitri; Nurlaily (Legal Standing : Jurnal Ilmu Hukum, 2026)
This study examines the legal issues surrounding the falsification of BPOM (Food and Drug Authority) registration numbers on processed food products through a comparative study between Indonesia and Malaysia. The main problems analyzed concern the differences in regulatory approaches between the two countries and the need for legal lessons that Indonesia can adopt to strengthen its consumer protection system. The research employs a normative juridical method using a statutory and comparative approach, based on the analysis of legislation, academic literature, and relevant research findings. The results show that legal protection in Indonesia remains indirect, fragmented across various regulations, and primarily focuses on repressive rather than preventive measures. In contrast, Malaysia has implemented a digital supervision system, adopted the principle of strict liability, and established stronger law enforcement through the National Pharmaceutical Regulatory Agency (NPRA). Normatively, this study concludes that Indonesia needs to establish specific provisions regarding the falsification of distribution permits in BPOM regulations or the Food Law, strengthen BPOM’s authority as the sole supervisory institution, and adopt a digital monitoring system to achieve effective, preventive, and technology-adaptive consumer legal protection.